A systematic review of the effectiveness of journal clubs in undergraduate medicine - Bello, Jibril O; Grant, Paul (Canadian Medical Education Journal, 2023)
Background: Training future doctors in the skills of evidence-based medicine (EBM) is clearly important. Journal club (JCs) are well-recognized educational interventions for teaching EBM. In contrast to postgraduate medical education, JCs use in undergraduate medical education (UME) has not been adequately explored. We conducted a realist review of the effectiveness of JCs in UME to unpack the underlying mechanisms by which the intervention works (or fails) in teaching EBM. Methods: The scope of review was the evaluation of the effectiveness of JCs in UME settings. We searched major bibliographic databases - MEDLINE, Embase, ERIC, PSYCInfo, CINAHL, Scopus, and Web of Science and found fifteen articles eligible for inclusion. Data was extracted aided by a modified Kirkpatrick framework and presented in evidence tables. Themes and chains of inference were identified, and finally, we formulated new hypotheses on how and why JC intervention works. Results: Mandatory vs. voluntary JC did not differentially impact attendance of JC in UME settings though JC duration beyond two hours decreased attendees’ self-reported satisfaction. Coupling lectures to JCs positively impacts knowledge gain and retention. Coupled Mentorship or using critical appraisal worksheets helped the achievement of manuscript writing skills and a positive attitude towards EBM. Conclusions: Journal clubs are effective interventions to teach EBM in UME settings and are well-received by learners. They improve specific learning outcomes of knowledge gain and retention, skills of manuscript writing and critical appraisal. However, we found no evidence that these translates to the practice of EBM nor impacts patient outcomes.